An Ignored Argument for Scientific Realism - Devitt, Michael (Filozofia Nauki, 2020)
Why believe in scientific realism? The answer that overwhelms the mainstream debate is “the no-miracles argument” (NMA): realism best explains the observational success of scientific theories. Yet more than thirty years ago another argument was proposed by Smart, Devitt, Glymour, McMullin, and Salmon and called “the basic argument” (BA) by Devitt: realism best explains the observed phenomena. Rather than having been addressed and assessed since, BA has been almost entirely ignored. The paper carefully distinguishes BA from NMA and argues that whereas NMA is dubious, BA is good. Why has BA been ignored? Experience suggests that philosophers may find it too close to science and mistakenly hanker after a “more philosophical” justification for realism. No such justification is needed or desirable.